RECEPTION ANALYST OF CRIMINALITY IN THE MOVIE PENYALIN CAHAYA - Lycho Daves Pradana; Rizca Haqqu (Jurnal Scientia, 2023)
Crime is an activity that violates specific rules and norms and is detrimental to other people which is still often found amid social life from the past until now. The Light Copyist is used as a research object because of his fame until now. This study uses a descriptive qualitative method with a constructivist paradigm and uses Stuart Hall's reception analysis theory as well as Soesilo's theory of crime and WA Bonger. This study aims to discuss the phenomenon of criminality in the film Copying Light based on Stuart Hall's 3 interpretive positions. There are 7 scenes analyzed and all of these scenes have elements of crime in them. Based on the answers from the informants, the majority of them are in a dominant-hegemonic position. In this study, there are new findings in the forms of crime that are not included in Bonger's classification and the emergence of crime levels, namely treason, felony, and misdemeanor. The researcher's suggestion is to continue this research regarding these new findings so that people become more aware of existing forms of crime.